PROFIL TOKOH REMAJA MINANGKABAU DALAM CERPEN-CERPEN REMAJA HARIAN UMUM SINGGALANG MINGGU - Hura, Chandra Firman; Hasanuddin WS, Hasanuddin WS; Nasution, Muhammad Ismail (Universitas Negeri Padang, 2014)
This study aimed to describe the profile in terms of adolescent Minangkabau outlook on life, responsibility, love, beauty, suffering and ideals of the juvenile short stories published by Daily Singgalang Sunday. Data were collected by means of : (1) read and understand short stories teen Singgalang daily publications Sunday, this is done to obtain a clear understanding of the profile of the studied adolescents , (2) record the speech and text can be abstracted as a teenager with profile data use a table format. Based on the research results, it can be concluded that the profile of adolescents in juvenile short stories published by daily Singgalang Sunday, has a live view of the ideal form of self behaved , responsible , family and love for the opposite sex , is able to conclude a beauty and also have pain. From the discussion, it can be seen, the profile figure in Minangkabau teen teen short story published Sunday daily Singgalang have a view of life that is included in the category of idealism, pragmatism and materialism.